Pengaruh Pupuk Majemuk NPK + Zn terhadap Pertumbuhan, Produksi dan Serapan Zn Padi Sawah di Vertisol, Sragen - Devangsari, Imas Masithoh; Maas, Azwar; Purwanto, Benito Heru (Universitas Muhammadiyah Yogyakarta, 2016)
Vertisol is a soil that has neutral to slightly alkaline pH. Zinc availability decreases with increasing pH. The existence of symptoms micronutrients scarcity, especially zinc, also caused by the use of highly yielding seeds with unbalanced fertilization. In addition, Zn uptake by plants is sustainability process which resulted in a decrease in nutrient levels of Zn in the root zone. The aim of the research was to determine the optimum Zn formula that can be added to the NPK compound fertilizer and to determine the effectiveness of the fertilizer on the growth and yield of rice. The experiment was arranged by completely randomized block design with 10 treatments and 3 replicates of each treatment. NPK compound fertilizer dose was given 300kg / ha. The result of this study showed that the compound fertilizer NPK + Zn had no effect on plant height, number of tillers and weight of the plant. The additional dose compound of 2% Zn to the dose of compound fertilizer NPK + Zn did not increase the yield. There was a tendency NPK treatment +0.75% Zn deliver the highest results. NPK compound fertilizer application + Zn significantly increased the uptake of Zn.